Promoting Responsible English Learning Trough Restitution Triangle and Local Values of Bugis Makassar at SMA Makassar Raya - Sugurawati Abubakar; Nurdin Noni; Baso Jabu (Hasanuddin University, 2025)
This study investigates how the integration of the Restitution Triangle with local wisdom from Bugis-Makassar culture supports the development of positive discipline in English learning. Conducted at a senior high school in Makassar, this qualitative study employed interviews, observations, and documentation to explore how students internalize responsibility and respectful behavior. The findings revealed that the implementation of restitution strategies, aligned with cultural values such as Sipakatau, Sipakainge', and Sipakalebbi, significantly contributed to students' behavioral awareness and self-regulation. The culturally adapted restitution model enabled students to reflect on their actions, repair harm, and engage actively in language learning. This research highlights the potential of combining restorative approaches with indigenous values to enhance classroom discipline and learner autonomy.